Measurement of maximal respiratory static pressure in stable COPD patients and their co-rrelation with various physiological anthropometric and spirometry parpmeters and arterial blood gas tension - Pradeep Kumar Vyas; Priyanka S Bindroo; Madhavi Gondha; Rajeev S Mathur; Gaurav Ghtawat; Vidyadhara Lakkappan (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
The strength of respiratory muscles can be evaluated from static measurement (PImax and PEmax) or inferred from dynamic measurement such as maximal voluntary ventilation. Maximal inspiratory pressure and Maximal expiratory pressure are simple, convenient and non-invasive measurement of respiratory muscle strength. Respiratory muscle strength decreases in COPD patients due to multiple factors. The primary aim of this study is to obtain mean PImax and PEmax values in Indian COPD patients and its co-rrelation with anthropomatric, physiological, spirometric parameters and arterial blood gas tension. Subjects and methods:  Retrospective data were collected between 2007to 2010.139 stable COPD patients of different stages according to GOLD classification were selected for this study with mean age 62.53 ± 10.36 years, out of 139 patients 104 were male and 35 were female. Results:  In our study mean PImax values in male and female COPD patients were 5.93 ± 2.19 kPa and 4.87 ±2.12 kPa respectively. Mean PEmax value in male and female COPD patients were 7.84 ± 2.80 kPa and 4.89 ±2.34 kPa respectively. Conclusion: In our study PImax, PEmax were reduced in COPD patients in comparison to normal populations and significantly lower in patients with severe airflow limitations than mild airflow limitations. This can help in assessment and monitoring of the disease burden, severity of functional impairment and response to treatment. It had significant positive or negative correlation with anthropometric and spirometry parameters and arterial blood gas tension.